Chemical Manipulation of Delayed Parturition in Captive Asiatic Elephant at Mysore Zoo - Raju, R.; Gopal Rao, B. S.; Khadri, S. M.; Asha, D. (Indian Forester, 1997)
Parturition with anterior presentation is most common among the mammals: Sometimes because of abnormalities, positioning of the foetus may result in dystocia. A case of cow Elephant of Mysore Zoo whose parturition process got delayed because of the partial uterine inertia trcated with 20 ml of Oxytocin 0.5% vol/wt intravenously with 500 ml of Dextrose 0.5% gave good response.